Austerity Britain, poverty management and the missing geographies of mental health. (July 2020) - Lowe, James; DeVerteuil, Geoffrey
Abstract: This paper presents the lived experiences of individuals with mental illness as they navigate the benefits landscape in an age of welfare reform in the UK. We focus on the impacts upon their well-being and daily geographies. We articulate the relationship between welfare reform and mental health using the concept of poverty management and its 'missing geographies', in which everyday well-being and routines are dismissed by the restructuring welfare system. We liken this dismissal to a shift towards a narrower and more unforgiving mode of poverty management, where even the smallest misstep can unravel the entire edifice of everyday survival and well-being. Highlights: This paper presents the lived experiences of individuals with mental illness as they navigate the benefits landscape in austerity Britain. The focus is on how benefits reform impacts upon the well-being and daily geographies of 25 individuals with mental illness. . The results speak to how benefits reform engenders a more narrow and unforgiving poverty management, leading to a raft of missing geographies. .